Use of an IoT Technology to Analyse the Inertial Measurement of Smart Ping-pong Paddle - Kanth Rajeev; Korpi Tuomas; Heikkonen Jukka (India, 2022)
In this article, a Smart Ping Pong Paddle has been introduced as an example of the use of sensor technology in sports. We have devised an accelerometer and a gyroscope sensor for the analyzing purpose and have gathered motion data of the game object to make a real-time 3D replica of the paddle to get an actual orientation of it. Technical details and principles of how to get the digital motion processing data from sensor to microcontroller and again transfer that wirelessly to a 3D modeling software are examined. Technical details are applied in practice, and the working demo of Smart Ping Pong paddle is built. Also, a couple of examples of other similar applications in the realm of object orientation sensing are overviewed.
Computer Science & Information Technology: 9th International Conference on Information Technology Convergence and Services (ITCSE 2020) May 30~31, 2020, Vancouver, Canada